OLIG2 mediates a rare targetable stem cell fate transition in sonic hedgehog medulloblastoma - Kinjal Desai; Siyi Wanggou; Erika Luis; Heather Whetstone; Chunying Yu; Robert J. Vanner; Hayden J. Selvadurai; Lilian Lee; Jinchu Vijay; Julia E. Jaramillo; Jerry Fan; Paul Guilhamon; et al. (Nature Communications)
Abstract Functional cellular heterogeneity in tumours often underlies incomplete response to therapy and relapse. Previously, we demonstrated that the growth of the paediatric brain malignancy, sonic hedgehog subgroup medulloblastoma, is rooted in a dysregulated developmental hierarchy, the apex of which is defined by characteristically quiescent SOX2+ stem-like cells. Integrating gene expression and chromatin accessibility patterns in distinct cellular compartments, we identify the transcription factor Olig2 as regulating the stem cell fate transition from quiescence to activation, driving the generation of downstream neoplastic progenitors. Inactivation of Olig2 blocks stem cell activation and tumour output. Targeting this rare OLIG2-driven proliferative programme with a small molecule inhibitor, CT-179, dramatically attenuates early tumour formation and tumour regrowth post-therapy, and significantly increases median survival in vivo. We demonstrate that targeting transition from quiescence to proliferation at the level of the tumorigenic cell could be a pivotal medulloblastoma treatment strategy.